Mediatization of Islamic Religious Teachings for the Deaf: Problems and Handling Strategies in East Java - Ngainun Naim; Rizqa Ahmadi; Yuni Roslaili; Ghinanjar Akhmad Syamsudin (Tribakti: Jurnal Pemikiran Keislaman, 2026)
Deaf people face serious challenges in the context of Islamic religious learning. Inappropriate Islamic religious teachings result in an incomplete understanding of the teachings that must be practiced in daily life. In some cases, this incomplete understanding leads to behavior that is inappropriate or even contradictory to Islamic religious teachings. This study aims to identify various problems faced by deaf people and the strategies for mediatizing Islamic religious teachings to optimize their acceptance of these teachings. This study was conducted in East Java. The method used was qualitative, with data collection techniques involving interviews, observation, and documentation. This study finds that the fundamental problems faced by deaf people include cultural issues, psychological issues, family parenting patterns, negative stigma, and unsupportive policies. Possible mediatization strategies include using a humanitarian approach to convey religious messages, creating a system that supports the acceptance of Islamic religious materials, optimizing the role of the Ministry of Religious Affairs, and optimizing the role of Islamic community-based organizations. The solution should be implemented according to a disability-centred paradigm, which encompasses both social and religious dimensions. Religious experience involving the body, sign language, and media constitutes a lived and embodied Islamic approach for Deaf people.